The Civilian War : Confederate Women and Union Soldiers during Sherman's March - Frank, Lisa Tendrich (Book collections on Project MUSE., 2015)
LISA TENDRICH FRANK received her Ph.D. in history from the University of Florida. She is the author and editor of numerous works relating to the Civil War, including Women in the American Civil War and the forthcoming The World of the Civil War: A Daily Life Encyclopedia.